The Theatre of Regret : Literature, Art, and the Politics of Reconciliation in Canada - Gaertner, David, 1979- (Book collections on Project MUSE., 2020)
"The Canadian public largely understands reconciliation as the harmonization of Indigenous-settler relations for the benefit of the nation. But is this really happening? Reconciliation politics, as developed in South America and South Africa, work counter to retributive justice. The Theatre of Regret asks whether - within the contexts of settler colonialism - this approach will ultimately favour the state over the needs and requirements of Indigenous peoples. Interweaving literature, art, and other creative media throughout his analysis, David Gaertner questions the state-centred frameworks of reconciliation by exploring the critical roles that Indigenous and allied authors play in defining, challenging, and refusing settler regret. In 2007, Canada became the first liberal democracy to formally implement a Truth and Reconciliation Commission (TRC) process, a prominent element of global intrastate politics in the 1990s. Through close examination of core concepts in reconciliation theory - acknowledgement, apology, redress, and forgiveness - Gaertner unpacks reconciliation within the contexts of Canadian settler colonialism and the international history of the TRC. In so doing, he exposes the deeply embedded colonial ideologies that often define reconciliation in settler colonial states. The Theatre of Regret redirects current debates about reconciliation and provides a roadmap for the deconstruction of state-centred discourses of regret."--